Investigation of Early Corrosion Behavior of Canister Candidate Materials in Oxic Groundwater by the EQCM Method - Gha-Young Kim; Sung-Wook Kim; Junhyuk Jang; Seok Yoon; Jin-Seop Kim (Science and Technology of Nuclear Installations)
This study investigated the corrosion mass changes of canister candidate materials (Cu, Ni, Ti, SS304) in an oxic groundwater solution using the electrochemical quartz crystal microbalance method in order to estimate corrosion thickness. The materials were immersed in naturally aerated groundwater with and without the addition of chloride ions to observe the mass changes as well as the open-circuit potential (corrosion potential). In the oxic groundwater solution, Ni, Ti, and SS304 exhibited negligible mass changes, indicating their insusceptibility to general corrosion. In contrast, the Cu electrode exhibited a relatively significant mass change (63.8 ng/cm2 for 60 h), and the maximum corrosion thickness was estimated to be approximately 0.1 μm/yr. In the presence of chloride ions, the Ni and Ti electrodes did not reveal demonstrate any significant changes, whereas the SS304 electrode was slightly increased compared to an absence of chloride ions. A lower mass change occurred when the Cu electrode was immersed in the chloride-containing groundwater solution compared with the absence of chlorides because the dissolution of Cu as CuCl2− was involved in Cu2O formation.